Does Agricultural Sector Contribute to the Economic Growth in Case of Republic of Benin? - MOUSSA, Aboubakari (Journal of Social Economics Research, 2019)
Every nation has his own resources contributing to the well-being of population and the creation of wealth. The sector that contributes in the country growth is not unique, but there are some who require a close look because they have large contribution in the economic growth such as agriculture sector. The determinants of a country economic growth are a lot but contribute differently to the growth. In this paper, we will discuss the extent of agricultural sector to the economic growth in Republic of Benin and how much it contributes. We will use time series data from 1970 to 2016 and co-integration method considering the order of integration. The results reveal that the GDP per capita, agricultural value added and the human development index have long-run relationship. In addition, an expansion of agricultural sector will have a significant impact on the economy in the long-run and ameliorate the living condition of population.